THE IMPLEMENTATION OF ENGLISH PROGRAM AT SMK PESANTREN BINA INSAN MULIA CIREBON - Toyibal Urbaq; Ikariya Sugesti; Fitri Aprianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
The spread of religion in Indonesia happens in various ways. One of them is that Islam entered Indonesia through many media in its spread, one of which is through education. In Islam, the spread through education is known as pesantren education, which plays a very large role in the spread of Islam in Indonesia. Pesantren it self is a traditional Islamic education where under the guidance of a teacher who is usually called a kyai with students who live together who are usually called dormitories. The purpose of this study was to know the implementation of the English Program at Bina Insan Mulia Islamic Boarding School Vocational School and how is teacher perception of the English Program at Bina Insan Mulia Islamic Boarding School Vocational School. This study uses checklist observations and interviews to find out the teachers planning documentation and implementation applied by the teacher in learning activities in class. The results of the research show it can be concluded it is known that the implementation of the English language program at the Bina Insan Mulia Islamic Boarding School has contributed to English lessons. From the research observations of teachers who have prepared observations of learning activity assessments for each teacher, in which the observation sheets contain opening activities, core activities, and closing activities which contain points that must be carried out by each teacher.